The Psychology of Food Choice - Shepherd, Richard (CABI, 2014)
Food choice involves the selection and consumption of foods and beverages, considering what, how, when, where and with whom people eat as well as other aspects of their food and eating behaviours. Food choices play an important role in symbolic, economic and social aspects of life by expressing preferences, identities and cultural meanings. Food choices are important because they create consumer demand for suppliers in the food system who produce, process and distribute food (Sobal et al., 1998). Food choices also determine which nutrients and other substances enter the body and subsequently influence health, morbidity and mortality.